Slow Pyrolysis Of Palm Wastes And Properties Of Biochar Blended Coal Briquettes - Inuwa, Ibrahim Abdullahi (2017)
The disposal of large amount of agricultural residues in developing countries causes a detrimental effect to the environment. Thus, this study is aimed at converting oil palm wastes from oil palm mill, into briquettes to significantly reduce the consequences following the existing disposal system. In this study, pyrolysis experiments were conducted from 300°C to 700 °C with heating rate between 5°C/min to 30°C/min by a lab-scale pyrolysis system. The results obtained showed, the quantity and quality of products mostly depend on the pyrolysis parameters (temperature and heating rate). The calorific value and carbon content of PKS biochar were 28.27 MJ/kg and 72.42%, which is significantly greater than that of coal sample of 26.21 MJ/kg and 64.66%. While moisture and ash content in biochar is 1.02 mfwt% and 4.88 mfwt which is lower than that of coal with 7.40 mfwt% and 6.62 mfwt% respectively. The composite PKS biochar and pure coal (bituminous) are mixed with percentage compositions of 100:0,80:20, 70:30, 60:40, 50:50, 60:40, 70:30 and O: 100 respectively. A different proportion of2, 2.5, 3, 3.5 and 4% cassava starch for the total mass of the mixture were used as the binder. The different compressed pressure of 80, 90,100, 110 and 120 kg/cm2 at 2 dwell times was used. Among the briquettes samples tested p 100 contained lowest moisture of 2.56 mfwt% and ash of 5.36 mfwt% with highest fixed carbon of 54.49 wt %. The increase in pure coal into the blend has led to a reduction in the energy value of the briquette from 29.83 to 25.55 MJkg-l. Cassava used as binder portrayed an insignificant effect in the calorific values of the briquettes. In the water boiling test analysis showed, pure biochar briquette PIOO generates the highest temperature up to 920.67°C compared to biochar-coal mixture briquettes and pure coal sample.